Social Disparities in Maternal Smoking during Pregnancy - Kuntz, B.; Lampert, T. (Geburtshilfe und Frauenheilkunde, 2016)
Background: Maternal smoking during pregnancy represents a significant developmental risk for the unborn child. This study investigated social differences in maternal smoking behavior during pregnancy in mothers living in Germany. The study focused on maternal age at delivery, social status and migration background. Method: The evaluation of data was based on two surveys carried out as part of the German Health Interview and Examination Survey for Children and Adolescents (KiGGS) carried out in 2003–2006 and in 2009–2012. The study compared the information given by parents of children aged between 0 and 6 years who were born either in the period from 1996 to  2002 (KiGGS baseline study, n = 4818) or in the period from 2003 to 2012 (KiGGS Wave 1, n = 4434). Determination of social status was based on parental educational levels, occupational position and income. Children classified as having a two-sided migration background either had parents, both of whom had immigrated to Germany, or were born abroad and had one parent who had immigrated to Germany; children classified as having a one-sided migration background had been born in Germany but had one parent who had immigrated to Germany. Results: The percentage of children whose mothers had smoked during pregnancy was 19.9 % for the older birth cohort and 12.1 % for the younger birth cohort. In both birth cohorts, the probability of being exposed to tobacco smoke was twice as high for children whose mothers were aged < 25 years at delivery compared to the children of older mothers. Children from socially deprived families were most affected by smoking behavior, and the relative social differences were found to have even increased over time (KiGGS baseline study: OR = 6.34; 95 % CI = 4.53–8.86; KiGGS Wave 1: OR = 13.88; 95 % CI = 6.85–28.13). A two-sided migration background was associated with a lower risk of exposure to smoking. Conclusions: The KiGGS results are in accordance with the results of other national and international studies which have shown that the percentage of mothers who smoke during pregnancy is declining. Because of a change in the method how data are collected for the KiGGS survey (written questionnaire vs. telephone interview) the trend results must be interpreted with caution. Measures aimed at preventing smoking and weaning women off smoking should focus particularly on younger and socially deprived mothers.
Keywords: maternal smoking; pregnancy; social status; migration background; health inequality